AT PORTS AND IN CABINETS: REPRESENTATIVES OF THE BRAZILIAN EMPIRE AND THE INCENTIVE TO PORTUGUESE EMIGRATION (1835-1860) - Galvanese, Marina Simões [UNESP] (FapUNIFESP (SciELO), 2024)
This paper examines the role of Brazilian diplomatic representatives in Portugal in recruiting laborers and facilitating the migration of dispossessed Portuguese individuals to Brazil during the years of Regency and the early decades of the Second Reign. Drawing on documents from the Itamaraty Archive and Portuguese archives, we demonstrate that the search for a supplementary workforce in the 1830s resulted in the formation of a triad comprising consular agents, ship captains, and Brazilian employers, which enabled the transportation of impoverished migrants to the Empire. Additionally, the paper shows that Brazilian diplomats were tasked with influencing Portuguese emigration policies and recruiting artisans to the Navy and Army arsenals, thereby compelling enslaved urban laborers to the fields and ensuring the perpetuation of slavery.
NOS PORTOS E NOS GABINETES: REPRESENTANTES DO IMPÉRIO DO BRASIL EM PORTUGAL E O INCENTIVO À EMIGRAÇÃO PORTUGUESA (1835-1860)
Keywords: Diplomatic relations; migration policies; Portuguese immigration